Civilization and Culture of Delhi in the Characters of Deputy Nazir Ahmed and Mirza Farhatullah Baig: Comparative Review - Mohammad Khursheed Ali; Dr. Farzana Kokab (Zaban-o-Adab, 2021)
Deputy Nazir Ahmed is an Urdu novelist. He is known and regarded the pioneer of Urdu novel. But he is also a humorist and in his novels he presented culture of Delhi by created some characters; especially his humorous character “Mirza Zahir Dar Baig” is well known and popular. Mirza Farhatullah Baig is an essay writer and humorist he created some humorous characters in his essays and presented culture of Dehli by them. This article is a comparative study of Nazir Ahmad and Farhatullah Baig. The present study discusses highlights and investigates culture of Delhi by humorous characters.